Calvinism and Taiwan - Yang-En, Cheng (Theology today, 2009)
How has Calvinism been at work in the island state of Taiwan over the last four centuries? Does the extension of “international Calvinism” to a remote corner of Asia yield new forms of expression? This article aims to describe and analyze four paradigms of the Calvinist presence and manifestation, embodied in the work of the Dutch Reformed Church, the British and Canadian missions, and the indigenous Presbyterian Church in Taiwan during the successive rules of the Dutch, the late Ching Dynasty of China, the Japanese, and the Nationalist regimes. Over time, the Calvinist tradition has displayed enduring witness as well as nuanced adaptation in the various yet challenging contexts of early modern colonialism, paternal modernization, wartime trials, and indigenous democratization in Taiwan.